Regulation of Electric Bicycles in the Advancement of Transportation Technology Based on Indonesian Traffic and Road Transport Law No. 22 of 2009 - An’nisaa’ Tabani Cahyaning Ekwandi; Setiawan Noerdajasakti; Yuliati (Правові горизонти, 2025)
This study examines the regulation of electric bicycles in the context of advancing transportation technology, based on Indonesia's Traffic and Road Transport Law No. 22 of 2009. The growing popularity of electric bicycles highlights the urgent need for legal frameworks that address safety, infrastructure, and environmental concerns. Current regulations tend to focus on traditional motor vehicles, leaving a regulatory gap for new transport technologies like electric bicycles. This paper analyzes existing legal provisions and identifies challenges in integrating electric bicycles into Indonesia’s transportation system. The findings suggest that while the law recognizes electric bicycles, it lacks clear guidance on licensing, operational standards, and environmental policies. Strengthening the legal framework for electric bicycles is essential to support sustainable transportation and technological innovation in Indonesia.